Prognostic impact of Ki-67 in patients with gastric cancer—the importance of depth of invasion and histologic differentiation. Issue 25 (June 2017) - Ko, Gyung Hyuck; Go, Se-Il; Lee, Won Sup; Lee, Jeong-Hee; Jeong, Sang-Ho; Lee, Young-Joon; Hong, Soon Chan; Ha, Woo Song
Abstract : Abstract: Ki-67 protein is a cellular marker for proliferation. The role of Ki-67 as a prognostic biomarker has not been established in gastric cancer. The present study was performed to investigate the significance of Ki-67 expression as a biomarker in early gastric cancer (EGC). With tissue microarray for 320 patients with gastric cancer, we performed immunohistochemical staining for Ki-67. Its clinical significance was analyzed with adjustment via the propensity score-matching. For validation, we performed bootstrap resampling. The median follow-up duration was 72 months (range: 3–120 months). Ki-67-high group showed worse prognosis than Ki-67-low group in EGC (5-YSR, 78.9% vs 92.0%, P   =  .018), but not in advanced gastric cancer (AGC) (5-YSR, 58.5% vs 59.2%, P   =  .951). Interestingly, in the patients with well-differentiated histology, prognosis for Ki-67-high group was considerably worse than that for Ki-67-low group (5-YSR, 67.0% vs 94.4%, P   =  .012), but not in those with moderately differentiated ( P   =  .504) and poorly differentiated histology ( P   =  .905). In this cohort, there was a strong correlation between the proportion of EGC and well-differentiated histology (r  =  0.215, P   =  .002). Multivariate analysis also revealed that the high-Ki-67 expression serves as a poor prognostic factor in EGC (HR 4.346, 95% CI 1.397–13.515, P   =  .011), especially in the well-differentiated histology, but not in all the patients ( P   =  .171). Bootstrap resampling internally validated this result ( P   =  .011). This study suggests that Ki-67 expression may be a good biomarker for prognosis prediction for EGC with well-differentiated histologic type. Abstract : Supplemental Digital Content is available in the text